Community Empowerment through MSMEs as an Effort to Improve Community Welfare - Sujarwo Sujarwo; Fitta Ummaya Santi; Tristanti Tristanti; Favian Fandi Kusuma; Fairuz Syakila Basatin Arif (Jurnal Mamangan, 2025)
Empowerment public is effort in increase ability public for free from various problems, so that become independent community. Empowerment through MSMEs is Wrong one strategy in increase welfare society. Goal This research is: 1) To describe empowerment patterns public through MSMEs in the Village Gari Wonosari Gunungkidul that happened currently; 2) Formulate model conceptual empowerment public through MSMEs in the Village Gari Wonosari Gunungkidul. Approach this research is qualitative with type studies case. Data collection techniques using observation, documentation, and interview.Technique data analysis using stages data collection, data condensation, data presentation and data extraction Conclusion. The results of this study are: 1) the pattern of empowerment is revealed. public through MSMEs in the Village Gari Wonosari Gunungkidul; 2) Composition model conceptual empowerment public through MSMEs in the Village Gari Wonosari Gunungkidul